2015
DOI: 10.1007/s00396-015-3671-z
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of two imidazolium gemini surfactants with two model proteins BSA and HEWL

Abstract: Gemini surfactants and their interactions with proteins have gained considerable scientific interest, especially when amyloidogenic proteins are taken into account. In this work, the influence of two selected dicationic (gemini) surfactants (3,3′-[1,8-(2,7-dioxaoctane)]bis(1-dodecylimidazolium) chloride and 3,3′-[1,12-(2,11-dioxadodecane)]bis(1-dodecylimidazolium) chloride) on two model proteins, bovine serum albumin (BSA) and hen egg white lysozyme (HEWL), have been investigated. A pronounced and sophisticate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Such mechanism of interaction between a similar gemini surfactant and amyloid beta 1-40 peptide was proposed by Han et al 55 As Han's peptide was negatively charged, which signicantly supported interaction between surfactant micelles and peptide brils, we expect that higher concentration of gemini surfactants are required for effective interaction in a HEWL/ gemini surfactant system, as compared to Han's research. 56 From this point of view the greater surfactant concentration, the stronger the observed effect, as the efficiency of process of absorbing HEWL molecules into gemini micelles rises with more micelles attached to HEWL aggregates.…”
Section: Amyloid Aggregation Of Lysozyme With Other Surfactants In Bumentioning
confidence: 99%
“…Such mechanism of interaction between a similar gemini surfactant and amyloid beta 1-40 peptide was proposed by Han et al 55 As Han's peptide was negatively charged, which signicantly supported interaction between surfactant micelles and peptide brils, we expect that higher concentration of gemini surfactants are required for effective interaction in a HEWL/ gemini surfactant system, as compared to Han's research. 56 From this point of view the greater surfactant concentration, the stronger the observed effect, as the efficiency of process of absorbing HEWL molecules into gemini micelles rises with more micelles attached to HEWL aggregates.…”
Section: Amyloid Aggregation Of Lysozyme With Other Surfactants In Bumentioning
confidence: 99%
“…In conclusion, most of the tested DNA complexes with selected surfactants exhibit good transfection properties at p/n ¼ 2. It is also worth noting, that we have previously characterized the interaction of selected C 12 JC n surfactants 71,72 with bovine serum albumin (BSA), which is a component of FBS used in transfection tests.…”
Section: Transfection Testsmentioning
confidence: 99%
“…Chatterjee et al 31 using micro-calorimetry found that hydrophobic interaction dominates over electrostatic repulsion resulting in lysozyme-CTAB aggregate formation. The effect of gemini surfactant on lysozyme have also been reported previously, 19,32,33 however relatively less interaction studies have been made till now. The aim of the present study is to decipher the binding interaction of M 16 and G 16 on the conformational stability and antibacterial activity of HEWL.…”
Section: Introductionmentioning
confidence: 57%
“…Cationic surfactant can bind to the positively charged HEWL through weak electrostatic (with negatively charged residues like Glu and Asp) and strong hydrophobic interactions. However, its stabilizing effect on the secondary structure of HEWL is imparted may be due to the positive charge associated with it, as elucidated in a study by Gospodarczyk et al 32 The increase in a-helical content can be elucidated due to the formation of the hydrophobic linkage between the hydrophobic chains and non-polar residues present on HEWL causes a local increase in the a-helical content of the protein as also observed in a study by Gull et al 20 and Wang et al 48 In the case of G 16 , the stabilizing effect on HEWL cannot be attributed to the positive charge present on the two head groups. The reason for this discrepancy can be explained due to the presence of longer spacer group 17 which causes lower charge density on the surfactant and thus possibly it binds weekly with HEWL as compared to M 16 unlike of some reported observations with much smaller spacer group.…”
Section: Circular Dichroism Spectroscopymentioning
confidence: 99%